Effects of combined treatment with transcranial and peripheral electromagnetic stimulation on performance and pain recovery from delayed onset muscle soreness induced by eccentric exercise in young athletes. A randomized clinical trial - Keriven, Hugo; Sánchez Sierra, Alberto; González de-la-Flor, Ángel; García-Arrabé, María; Bravo-Aguilar, María; de la Plaza San Frutos, Marta; Garcia-Perez-de-Sevilla, Guillermo; Tornero-Aguilera, Jose Francisco; Clemente-Suarez, Vicente Javier; Domínguez-Balmaseda, Diego (Frontiers in Physiology, 2023)
Background: There is a common interest in finding a common consensus in the approach of athletes suffering from DOMS with the aim of accelerating recovery and thereby enhancing performance. The objective of this study was to observe the effects of a paired-associative transcranial and peripheral electromagnetic stimulation on young athletes suffering from DOMS, induced by 1 hour of eccentric and plyometric exercises. Methods: Forty-eight young athletes participated in this randomized control trial: 13 were assigned to the peripheral group (P); 12 were in the control group (Cont); 11 were assigned to the transcranial group (T) and 12 were included in the paired-associative group (Comb). The Visual Analogue Scale (VAS) of pain perception and the mechanical Pressure Pain Threshold (PPT) were the tools used to analyze the symptoms of DOMS. On the other hand, the Half Squat (HS) test evaluated with an accelerometer, and the 30 meters sprint velocity (30-mSP) test were used to observe the evolution of the sports performance of the lower limbs. All evaluations were performed before and after the eccentric exercise session that caused DOMS, as well as at 24-48, and 72 hours afterward. Results: The AS group improved the symptoms of the induced DOMS, since significant positive differences were observed in the VAS and PPT compared to the other groups (p<0.001). In addition, the AS group showed a significant improvement in the HS and the 30-mSP tests (p<0.001). Based on the results a treatment with both peripheral and transcranial electromagnetic stimulation improves recovery and performance in athletes at 72 hours, although these data would need to be verified in future research with a larger sample size. Conclusions: Paired-associative electromagnetic stimulation improved DOMS symptomatology, velocity, and sports performance in the lower limbs.